2018
DOI: 10.1029/2018gl079515
|View full text |Cite
|
Sign up to set email alerts
|

On the Sensitivity of the Relationship Between Hadley Circulation Asymmetry and ENSO in CMIP5 Models

Abstract: Recent study shows that the asymmetric component (AC) of Hadley circulation variability during late winter and early spring can be explained by the combined effect between background sea surface temperature (SST) and the SST anomalies associated with El Niño–Southern Oscillation (ENSO). But the sensitivity of AC‐ENSO relationship to background SST and ENSO properties is still unknown. Using 17 climate models from the Coupled Model Intercomparison Project phase 5, we investigated the sensitivity of the AC‐ENSO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…However, some studies reported several ozone depletion events in the Arctic stratosphere, which are comparable to that of the Antarctic ozone hole (e.g., Manney et al, 2011). Arctic stratospheric ozone (ASO) was suggested to influence the El Niño-Southern Oscillation (ENSO) events (Garfinkel, 2017;Xie et al, 2016Xie et al, , 2017, whereas ENSO could exert significant influences on the HC (e.g., Guo & Tan, 2018a, 2018b, 2018cWang, 2002). Thus, changes in the ASO might also have impacts on the HC in the Northern Hemisphere (NH).…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies reported several ozone depletion events in the Arctic stratosphere, which are comparable to that of the Antarctic ozone hole (e.g., Manney et al, 2011). Arctic stratospheric ozone (ASO) was suggested to influence the El Niño-Southern Oscillation (ENSO) events (Garfinkel, 2017;Xie et al, 2016Xie et al, , 2017, whereas ENSO could exert significant influences on the HC (e.g., Guo & Tan, 2018a, 2018b, 2018cWang, 2002). Thus, changes in the ASO might also have impacts on the HC in the Northern Hemisphere (NH).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there is a close relation between the ENSO and the HC (Huang et al, 2019). The intensification of the HC in the Northern Hemisphere (NH) and the changes in its dominant mode exhibit a significant relationship with the ENSO events since 1970 (Caballero, 2007;Guo and Tan, 2018a;Guo and Tan, 2018b;Wang et al, 2020). Such as, Oort and Yienger (1996) found that the intensity of the HC in the eastern Pacific is closely linked to the SST, where the intensity of the HC increases when ENSO is in its positive phase.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have interpreted that the equatorial quasi‐symmetric mode of the HC is connected to El Niño (e.g., Feng & Li, 2013; Ma & Li, 2008; Oort & Yienger, 1996). Meanwhile, it has been illustrated that the occurrence of El Niño events could contribute to the asymmetric mode of the HC (e.g., Feng et al., 2019; Guo & Tan, 2018a; Zhang & Wang, 2013). The equatorial asymmetric and quasi‐symmetric modes are linearly independent; however, both are related to the ENSO.…”
Section: Introductionmentioning
confidence: 99%